Market access, the skill premium and human capital in Spain (1860-1930) - Rafael González-Val; Pau Insa-Sánchez; Julio Martinez-Galarraga; Daniel A. Tirado Fabregat (European Historical Economics Society (EHES), 2022)
This paper explores the relationship between market access and education levels in the context of an industrializing economy, in this case Spain between the late nineteenth and early twentieth centuries. Specifically, we examine whether differences in regional accumulations of human capital could be related to market access, which would explain the divergent trajectories of regional economic growth in Spain. To do this, we empirically test the relationship between education variables and market potential for Spanish provinces between 1860 and 1930. We then focus on the mechanism that may be mediating this relationship, i.e. the skill premium. The results suggest that there were sizeable provincial differences in the return on investment in education, the explanation for which would be that those provinces with the highest market potential specialized more in skill-intensive sectors in which higher wages were paid.
Keywords: I25; N90; O15; R12; 330; Economic history; market access; human capital